2010
DOI: 10.1007/978-1-4419-6366-6_7
|View full text |Cite
|
Sign up to set email alerts
|

Contractile Characteristics of Sarcomeres Arranged in Series or Mechanically Isolated from Myofibrils

Abstract: The mechanisms of contraction are intrinsically connected to -sarcomere mechanics during muscle activation and relaxation. This chapter presents two sets of experiments performed with (1) myofibrils, in which individual sarcomeres in series can be evaluated during contractions, and (2) mechanically isolated sarcomeres. When activated at optimal length (approximately 2.0-2.4 μm), myofibrils and sarcomeres produce similar forces. However, their dependence on length differs: sarcomeres in series in a myofibril ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
15
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 49 publications
3
15
1
Order By: Relevance
“…Although the levels of nonuniformities and A-band displacements are larger during the experiment shown in the left, it is also present in the experiment shown in the right. muscle fibers (10,12,17,46) and myofibrils (41) and well described by the predictions of overlap between myosin and actin filaments (32,40). The forces produced by single sarcomeres in the current study are in the range of those observed with myofibrils (23,35,36), single fibers (6), and single sarcomeres (32).…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…Although the levels of nonuniformities and A-band displacements are larger during the experiment shown in the left, it is also present in the experiment shown in the right. muscle fibers (10,12,17,46) and myofibrils (41) and well described by the predictions of overlap between myosin and actin filaments (32,40). The forces produced by single sarcomeres in the current study are in the range of those observed with myofibrils (23,35,36), single fibers (6), and single sarcomeres (32).…”
Section: Discussionsupporting
confidence: 79%
“…1). The centroids of the peaks were detected by a minimum average risk (42), as used previously in experiments with isolated sarcomeres (32,40) and myofibrils (31,35,36).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations